2021
DOI: 10.1093/jaoacint/qsab063
|View full text |Cite
|
Sign up to set email alerts
|

Single- and Multiple-Laboratory Validation of LC-MS/MS Method for Simultaneous Determination of Fosetyl-Al and Phosphonic Acid in Cereal Grains and Analysis of Rice, Wheat, and Barley

Abstract: Background and objective In Japan, the residue definition for fosetyl-Al was “sum of fosetyl-Al and phosphonic acid expressed as fosetyl-Al” and its current provisional MRL in cereals was under review. For establishment and enforcement of fosetyl-Al MRL in cereals, a new analytical method for fosetyl-Al and phosphonic acid in cereals should be developed and validated. Methods The new method involved water extraction, clean-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…By analogy to that from the liquid matrices, the recovery from solid samples ranged from 83.2 to 108.2% across all samples. The trace recovery of our IC-ICP-MS-based method was in accordance with the values reported by Adams et al, Bauer et al, and Sekiyama et al, who found recovery rates of 94–106, 80–106, and 88–96% of phosphonic acid in trace amounts of different food matrices (e.g., apple, lemon, avocado, wheat) after a single extraction, respectively. A slight overestimation was found for CD detection in sediment (107.3 or 108.2%) due to the high presence of tartrate precipitating in the must.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…By analogy to that from the liquid matrices, the recovery from solid samples ranged from 83.2 to 108.2% across all samples. The trace recovery of our IC-ICP-MS-based method was in accordance with the values reported by Adams et al, Bauer et al, and Sekiyama et al, who found recovery rates of 94–106, 80–106, and 88–96% of phosphonic acid in trace amounts of different food matrices (e.g., apple, lemon, avocado, wheat) after a single extraction, respectively. A slight overestimation was found for CD detection in sediment (107.3 or 108.2%) due to the high presence of tartrate precipitating in the must.…”
Section: Resultssupporting
confidence: 91%
“…Further recent analytical approaches focused on liquid chromatography electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) methods for the simultaneous determination of polar pesticides including phosphonate. One pitfall of this method is that an important negative ion mass transition of phosphonic acid ( m / z 81 → 63) is also observed as a minor transition of phosphoric acid, which can lead to major interferences in case of insufficient chromatographic separation. To solve this problem, an alternative mass transition for phosphonic acid ( m / z 81 → 79) has been recommended, particularly because the chromatographic resolution between these related compounds is often poor in the presence of high amounts of phosphoric acid or its anion, as found in grapes and grapevines .…”
Section: Introductionmentioning
confidence: 99%
“…For SPE, the performance of different commercial SPE cartridges was evaluated. The result indicates that combining mixed-mode cation-exchange (MCX) and enhanced matrix removal (EMR) can give the best recovery and the lowest matrix effect of HPP residues in oats [ 14 , 23 , 24 ]. Another easy way to precipitate unwanted coextracts is by freezing the extracts [ 15 ].…”
Section: Sample Preparationmentioning
confidence: 99%
“…This technique enables sample pretreatment and analysis to be completed at the same time. In addition, an ion exchange mini column can also be utilized as a sample clean-up method for quantifying fosetyl-Al and phosphonic acid in rice, wheat, and barley [ 23 ].…”
Section: Sample Preparationmentioning
confidence: 99%
“…In many countries, fosetyl and its aluminum salt (fosetyl-Al) are systemic fungicides used to control oomycetes and ascomycete fungi, as well as some plant pathogenic bacteria, in fruit trees, vegetables, and ornamental plants [10]. Glyphosate (N-phosphonomethyl glycine) is a nonselective postemergence herbicide used to control a wide variety of grass and broad-leaf-weed species in agricultural and industrial settings [11].…”
Section: Introductionmentioning
confidence: 99%